Fraksinasi dan identifikasi senyawa volatil asap cair cangkang sawit=(fractionations and identification of volatile compounds of liquid smoke - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT Palm kernel shell is one residue material of oil palm process industry. Total palm kernel shell were sufficient and could be processed into liquid smoke. The liquid smoke has been found to contain compounds functioning as smoky product improvement. This research was to identify volatile compound components existing in the liquid smoke of pabn kernel shell. This research started from liquid smoke production by pirolisa at 400 Â°C for 90 minutes and fractionation of temperature variation